(untitled) (Fiep Bulletin - online, 2013)
This study aimed to check how the morphological values in bus drivers aged 25 to 57 years have varied at a two-year interval. Several national and international studies have shown that the bus drivers fall in ill and die in a different way than population in general. The study was observational, scored during two consecutive years and consisted of observations, at three different times, by assessing height-weight values, body composition, waist-hip ratio and BMI. The study sample consisted of 179 male subjects, aged 25 to 57 years, all of them bus drivers belonging to a company of interstate transportation from Bahia, Brazil. The subjects were split into five according to age group. The collected data were entered into a computer program SPSS 11.0 in order to apply the statistical methods. In analyzing the data we found that the bus drivers showed unfavorable results for health indicators, showing as cited in several studies in other countries, that this occupation affects and increases the susceptibility of an individual to develop or promote any chronic degenerative disease. Through physical assessments conducted, the individuals presented in general, an improvement in their health indicators over a time, and even with these data, we highlight the need to implement programs to promote health and better working conditions for these workers.